Imaging Guided Endogenic H2‐Augmented Electrochemo‐Sonodynamic Domino Co‐therapy of Tumor in Vivo. Issue 9 (20th January 2023) - Qi, Guohua; Yu, Tengfei; Li, Jianmei; Guo, Zirui; Ma, Kongshuo; Jin, Yongdong
Abstract: Precise and on‐demand release of sufficient hydrogen (H2 ) to tumor sites remains a key challenge for emerging H2 ‐oncotherapy, and little is known about the physiological effects of "abundant" H2 on complex tumor microenvironments (TME). Here, a highly efficient and cost‐effective imaging‐guided/‐assessed H2 ‐therapy of tumors based on a joint electrochemo‐sonodynamic treatment (H2 ‐EC/SD co‐therapy) with strong "domino effect" triggered by endogenous H2 generation at tumor sites is reported to speedily eliminate tumor tissue (≤80 mm 3 ) within 1 day. Adequate H2 is controllably generated in tumor sites through mild electrochemistry in vivo due to acidic TME by using clinical acupuncture Fe needles as electrodes. Besides starvation damage due to gas blockage/destruction of vessels, nano‐/micro‐bubbles of H2 formed in situ can elevate the tumor's internal temperature and burst vessels to further destroy the tumor under ultrasound irradiation. Remarkably, vulnerable homeostasis of TME is disturbed as H2 also participates in the physiological activity of tumor cells, leading to tumor dysfunction. Last but not least, the body's inflammatory response to cancer is reduced after the treatment, which is beneficial for the body's immune system during post‐treatment recovery. Based on all of these merits, the H2 ‐EC/SD co‐therapy provides a potentially safe and viable therapeutic strategy for future clinical applications. Abstract : A highly efficient and cost‐effective imaging‐guided/‐assessed H2 ‐therapy of tumors based on a joint electrochemo‐sonodynamic treatment (H2 ‐EC/SD co‐therapy) is developed. The endogenic H2 ‐triggered "domino effect" in tumor tissue is clearly revealed. The developed H2 ‐EC/SD co‐therapy guided by US imaging in vivo will open up a feasible new way for green, economic, and effective treatment of cancer in the future.